PRIMARY HYPERALDOSTERONISM: A LONG ROAD TO DIAGNOSTICS AND EFFECTIVE TREATMENT (CLINICAL CASE) - Каширина, Евгения Петровна; Королёва, Юлия Борисовна; Каширина, Елена Жоржевна; Хохлов, Константин Сергеевич (Medicine in Kuzbass, 2023)
Primary hyperaldosteronism (PHA), which was considered a rare disease, according to the results of studies, is the cause of arterial hypertension (AH) in 5-15 % of cases, which puts it in the first place in the structure of secondary hypertension. PHA is a serious disease, since high values of aldosterone, in addition to its indirect effect, have a direct damaging effect on the myocardium, blood vessels, and renal interstitium. Timely diagnosis allows you to either completely cure the patient of hypertension, or use effective therapy. This clinical observation confirms the importance of timely diagnosis, surgical treatment.
Keywords: primary hyperaldesidism; aldosteroma; arterial hypertension; aldosterone; adrenal glands